Minding creation: theological panpsychism and the doctrine of creation - Leidenhag, Joanna (T & T Clark studies in systematic theology, 2021)
"Are humans the only ones who can appreciate God's creation? What if consciousness is spread more widely across all things? Looking at panpsychism through the lens of Christian doctrine, this volume is the first substantial examination of what theory of consciousness implies for key theological debates concerning God's presence and action, evolution and the origin of the soul, human uniqueness and the environmental crisis. Joanna Leidenhag develops a theological panpsychism that is based on an exceptionally wide range of scholarship. Minding Creation brings together the theologies of Augustine of Hippo, Gottfried von Leibniz and other major figures, and the philosophy of such contemporary thinkers as Thomas Nagel, Galen Strawson and David J. Chalmers. Leidenhag also discusses key concepts and issues, such as emergence theory and ecology. She concludes that God created a universe from nothing which is filled with indwelling powers, sacramental value, and intrinsic experience. This is a creation in which the Holy Spirit is internally present at every point, a creation that worships God, and a creation that human beings must protect and lead in praise"--